Assessing trophic interactions between pelagic predatory fish by gut content and stable isotopes analysis around Fernando de Noronha Archipelago (Brazil), Equatorial West Atlantic - Martins, Karla; Pelage, Latifa; Justino, Anne K. S.; Frédou, Flavia Lucena; Júnior, Teodoro Vaske [UNESP]; Le Loc'h, François; Travassos, Paulo (Wiley, 2021)
The objective of this study was to analyse the feeding habits and trophic interactions between four oceanic predatory fish around the Fernando de Noronha Archipelago (FNA), Brazil, in the western equatorial Atlantic (3.86°S/32.42°W), internationally recognized as an environment of high economic and ecological value. For this purpose, biological samples of yellowfin tuna (Thunnus albacares), wahoo (Acanthocybium solandri), barracuda (Sphyraena barracuda) and dolphinfish (Coryphaena hippurus) were collected for stomach content and stable isotope analysis. Values of the index of relative importance revealed varied diets, with a strong presence of teleost fishes (Diodontidae and Exocoetidae) for all species, with yellowfin tuna having a greater diversity of food items. Despite being generalists/opportunists, the feeding strategy of these predators showed a tendency towards a specialized diet in the use of the available resources around the FNA. They presented a narrow trophic niche width (Levin's index, Bi < 0.6) and low overlap between species, except between barracuda and wahoo (MacArthur and Levin's, R0 = 0.72). Isotopic compositions had broad values of δ13C and δ15N, and were significantly different between species. Our results provide information about the four species' trophic organization and suggest that the predators avoid competition by preying on different prey, thus allowing their coexistence.
Keywords: stable isotope; stomach content; trophic ecology; tuna; Western equatorial Atlantic